Separation of iridium(IV) and rhodium(III) from hydrochloric acid solution by solvent extraction with Cyanex 921. Issue 4 (4th July 2018) - Le, Minh Nhan; Lee, Man Seung
ABSTRACT: The separation of Ir(IV) and Rh(III) by solvent extraction with Cyanex 921 was investigated in the HCl concentration ranges from .1 to 9 M. Ir(IV) was selectively extracted over Rh(III) by Cyanex 921 in the experimental ranges. Ir(IV) extraction was greatly affected by HCl concentration, while Rh(III) extraction was insensitive to HCl concentration. The highest separation factor between Ir(IV) and Rh(III) was obtained at 1 M HCl solution. The addition of TBP prevented the formation of a third phase and improved phase separation. Both metals ions were completely stripped from the loaded Cyanex 921 by HCl, (NH4 )2 S2 O3, NH4 Cl, NaSCN, HClO4, NaOH, and (NH2 )2 CS, while employment of (NH4 )2 S2 O3 solution led to selective stripping of Ir(IV) over Rh(III). A process for the separation of Ir(IV) and Rh(III) can be developed by extraction with Cyanex 921 followed by stripping with (NH4 )2 S2 O3 .